Analisis Manajemen Modal Kerja PT. Sri Rejeki Isman Tbk Periode Tahun 2016-2018 - Fanniya Dyah Prameswari; Suhaji Suhaji; Lita Apriani Rustian (STIE Widya Manggala, 2022)
As a company that produces textiles, PT. Sri Rejeki Isman, Tbk, has working capital that must be managed efficiently. To find out how to manage working capital, this study uses activity ratio as an indication that working capital has been managed properly or not. Based on the calculation of several types of activity ratio, the management of working capital management of PT Sri Rejeki Isman Tbk is still quite efficient. In the measurement of working capital turnover, the company’s average working capital turnover is greater than the industry standard average. For the total asset turnover ratio, the company experiences a low rating compared to the average textile industry standard in Indonesia. As for the assessment of the ratio of inventory turnover and account receivable turnover, the company is able to manage its inventory and receivables quite well.